Cyclophilin A modulates bone marrow-derived CD117+ cells and enhances ischemia-induced angiogenesis via the SDF-1/CXCR4 axis. (1st June 2016) - Perrucci, Gianluca L.; Straino, Stefania; Corlianò, Maria; Scopece, Alessandro; Napolitano, Monica; Berk, Bradford C.; Lombardi, Federico; Pompilio, Giulio; Capogrossi, Maurizio C.; Nigro, Patrizia
Abstract: Background: Critical limb ischemia (CLI) is a major health problem with no adequate treatment. Since CLI is characterized by insufficient tissue vascularization, efforts have focused on the discovery of novel angiogenic factors. Cyclophilin A (CyPA) is an immunophilin that has been shown to promote angiogenesis in vitro and to enhance bone marrow (BM) cell mobilization in vivo . However, its potential as an angiogenic factor in CLI is still unknown. Thus, this study aimed to evaluate whether CyPA might induce neo-angiogenesis in ischemic tissues. Methods and results: Wild-type C57Bl/6j mice underwent acute hind-limb ischemia (HLI) and received a single intramuscular administration of recombinant CyPA or saline. Limb perfusion, capillary density and arteriole number in adductor muscles were significantly increased after CyPA treatment. Interestingly, BM-derived CD117 + cell recruitment was significantly higher in ischemic adductor tissue of mice treated with CyPA versus saline. Therefore, the effect of CyPA on isolated BM-derived CD117 + cells in vitro was evaluated. Low concentrations of CyPA stimulated CD117 + cell proliferation while high concentrations promoted cell death. Moreover, CyPA enhanced CD117 + cell adhesion and migration in a dose-dependent manner. Mechanistic studies revealed that CyPA up-regulated CXCR4 in CD117 + cells and in adductor muscles after ischemia. Additionally, SDF-1/CXCR4 axis inhibition by the CXCR4 antagonist AMD3100 decreased CyPA-mediated CD117 + cell recruitment in the ischemic limb. Conclusion: CyPA induces neo-angiogenesis by recruiting BM-derived CD117 + cell into ischemic tissues, at least in part, through SDF-1/CXCR4 axis.